Biology and Management of Eggplant Fruit and Shoot Borer, Leucinodes orbonalis Guenee (Lepidoptera: Pyralidae) - Mainali, Ram Prasad (International Journal of Applied Sciences and Biotechnology, 2014)
Eggplant (Solanum melongena Linnaeus) is one of the most economically important vegetable of tropics having hot-wet climate. The key pest, eggplant fruit and shoot borer, Leucinodes orbonalis Guenee found to be most destructive and first ranked threat especially in South Asia, hence become hot issue for research in this region. It inflicts sizeable damage up to 80 percent in terms of fruit and content of vitamin-C. This situation refrained the farmers growing eggplant, hence relevant literature were gleaned and overviews regarding biology and management of borer with supportive facts and figure for safe and healthy eggplant production. As integrated approaches of pest management have been gaining popularity nowadays, this article outlines all the components of IPM including use of resistant varieties, sex pheromones, cultural methods, physical and mechanical barriers, bio-pesticides and bio-control agents, botanical and chemical means of management including basic biological parameters associated with management. DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.10001 Int J Appl Sci Biotechnol, Vol. 2(1): 18-28